2013
DOI: 10.1063/1.4801997
|View full text |Cite
|
Sign up to set email alerts
|

Temperature–electric field hysteresis loop of electrocaloric effect in ferroelectricity—Direct measurement and analysis of electrocaloric effect. I

Abstract: The polarization of polar domain in ferroelectric materials is orientated and reversed with the alternating electric field, and the hysteresis loops of polarization-electric field (P-E) and strain-electric field (S-E) are observed. For electrocaloric (EC) effect, the temperature change with the application and removal of electric field is also attributed to the change of polarization with the applied field. In most reports about EC, the temperature change is shown as an abrupt jump or slump due to the applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 13 publications
0
35
0
Order By: Relevance
“…For instance, a recent study using non-adiabatic direct measurement on PZT-5 ceramics showed that DT displays a hysteresis behavior with E and the sign of electrocaloric effect reverses at the coercive field where polarization switching occurs. 105 Using a phase field method, similar DT-E curves were predicted in PbTiO 3 nanoparticle in which vortex domain switching was considered. 106 Moreover, phase field theory predicted a sign reversal of electrocaloric response at the domain walls (180 in Ref.…”
Section: F Heat Capacity and Kineticsmentioning
confidence: 97%
See 2 more Smart Citations
“…For instance, a recent study using non-adiabatic direct measurement on PZT-5 ceramics showed that DT displays a hysteresis behavior with E and the sign of electrocaloric effect reverses at the coercive field where polarization switching occurs. 105 Using a phase field method, similar DT-E curves were predicted in PbTiO 3 nanoparticle in which vortex domain switching was considered. 106 Moreover, phase field theory predicted a sign reversal of electrocaloric response at the domain walls (180 in Ref.…”
Section: F Heat Capacity and Kineticsmentioning
confidence: 97%
“…26,59,60,62,128,138 Otherwise, thermal losses may lead to the measurements conducted in non-adiabatic conditions. 105 The thermocouple or thermometer by itself cannot be used to provide reliable determination of the electrocaloric effect in thin films and is sensitively influenced by the surroundings. However, it can be integrated into a calorimeter system (i.e., high-resolution calorimeter 11,58,124,139 and scanning thermal microscope 104,138 ) as one of the key elements to achieve highresolution probe of the electrocaloric effect even in thin films.…”
Section: A Thermocouple and Thermometermentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12][13][14][15] Over all, the studies on ECE are mainly concentrated on the FE (or AFE)-paraelectric (PE) switching process, because of the large entropy change and the considerable pyroelectric effect caused by the structure phase transition. In fact, the phase transition between AFE and FE could also bring a large entropy change, and is easily realized at near room temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…[18] Among these samples, it is estimated that the PZT ceramics with Tc of 140 C exhibited largest ΔT. [19] Considering that both ECE and field-induced displacement derive from the change in polarization, the similar appearance of the loops is reasonable. The temperature changes in PZT ceramics induced by bipolar switching field of 30kV/cm were 0.2K and 0.15K, respectively.…”
Section: Methodsmentioning
confidence: 78%